Employees Aren’t Factory Slaves: Factors Determining Work Demand and Implications for HRM Practices - Kengatharan, N. (Sciedu Press, 2019)
Although a plethora of studies on factors determining work demand have been investigated in the West, the Western findings cannot be directly applied to another cultural context and there is still rather constraint studies in collectivist cultural nations. Drawing on the conservation of resources theory and Hofstede’s cultural framework, the present study aims to fill a lacuna by identifying factors determining work demand in a collectivist cultural context. Anchored in ontological and epistemological assumptions, the study employed hypothetic-deductive approach with a survey strategy. Data were garnered from randomly selected 569 employees working in the banking sector with the aid of a self-administrated questionnaire. The results disclose that males work longer hours and experience greater work demand than females. The study further reveals the predictors of work demand: working hours had shown the largest impact, followed by tenure, gender, income, formal work-life policies and supervisory status. The present study questioned the worthiness of the equal policies for both men and women in the workplace and emphasised the needs for gender-based HR policies. On balance, the study pushes back the frontiers of work-family literature and becomes a springboard to future scholarly works.
Keywords: Work demand; Work-life policies; Supervisory status; Conservation of resources theory; Hofstede’s cultural framework